(untitled) (CIENCIA Y TECNOLOGÍA AGROPECUARIA, 2025)
Biological collections are veritable treasures of information that provide an invaluable historical perspective on biodiversity. These collections play an important role in various fields, both in research from taxonomy and ecology to the conservation of biodiversity. Thanks to biological collections, it is possible to find a source of historical record where covers the distribution and composition of different species over the years, in addition, by preserving these specimens, researchers can compare biological diversity at different times, which makes it possible to detect changes and/or loss of genetic diversity. To this end, a research was carried out with a descriptive non-experimental field design in 120 hectares of the María Lucia Metropolitan Park of the University Corporation of Meta. The biological collection of lepidoptera, being an important component in ecosystems, provides valuable information on biodiversity, climate effects and anthropogenic impacts. On the other hand, these biological collections play a crucial role in terms of education and scientific dissemination, so that in academic institutions they are not simply stores of specimens, living repositories that document the rich diversity of a specific region. The collections foster a greater understanding and appreciation of nature, in a world where biodiversity is threatened, these riches of information not only store the past but also guide the future of environmental conservation.